1993
DOI: 10.1182/blood.v82.12.3580.bloodjournal82123580
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a 5-fluorouracil-enriched osteoprogenitor population of the murine bone marrow

Abstract: In the presence of beta-glycerophosphate and vitamin C, cultures of normal mouse bone marrow cells form three-dimensional structures that stain positive with the Von Kossa technique and express alkaline phosphatase (ALP), collagen type I, and osteocalcin. Little is known about the characteristics and frequency of the cells that contribute to this phenomenon. Most likely, mature osteoblastic cells do not contribute to the nodule formation because no osteocalcin expressing cells are detected in the flushed marro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 0 publications
3
40
0
Order By: Relevance
“…Several purification strategies for the isolation of early osteoblast precursors from BM stroma have been described. (22,31,42,43) However, in these studies the cells were maintained in short-term cultures and no clonal cell lines were generated. In this report, we describe for the first time the isolation and establishment of immortalized clonogenic human osteoprogenitor cells immunoselected from fetal human BM stroma.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several purification strategies for the isolation of early osteoblast precursors from BM stroma have been described. (22,31,42,43) However, in these studies the cells were maintained in short-term cultures and no clonal cell lines were generated. In this report, we describe for the first time the isolation and establishment of immortalized clonogenic human osteoprogenitor cells immunoselected from fetal human BM stroma.…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of WGA or other lectins, 80% of BM cells agglutinate and form clusters that sediment, and previous studies have shown that majority of stromal progenitors (WGA + ) reside in this agglutinated fraction, (23,33) whereas hematopoietic lineage cells and their progenitors have no lectin-binding sites on their cell surface. (22,35,36) Osteoprogenitors can be sorted from mouse BM based on their binding to WGA and Sca-1 expression. (31) Sca-1 antigen is coexpressed by cells of both stromal and hematopoietic lineage (CD34 + ) cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this experimental set-up, cells are obtained from the central bone marrow compartment, whereas cells at the bone surface do not detach and are not included. (29) Bone marrow cells were resuspended in 0.9 ml of 4 M guanidinium isothiocyanate lysis buffer and stored at Ϫ20°C until RNA isolation. Bone marrow RNA was isolated according to the method described by Chomczynski and Sacchi.…”
Section: Isolation Of Cellular Rnamentioning
confidence: 99%